Sovereignty’s Sonic Limits: Music and Spectacle at the Border - Gabriel Mindel (Studies in Social Justice)
Despite the wide proliferation of bordering processes across places, platforms, and populations, movements for border justice often maintain a materialist and geographically narrow focus. Activists draw public attention to the border’s physical infrastructure, challenging the use of barriers, policing, and incarceration to violently prevent and punish transnational migration. To counter this “border spectacle” enacted by the State (De Genova, 2013), protest against contemporary border regimes may take its own spectacular form, whether as sabotage, blockading and disruption, or as humanitarian interventions. Border resistance may also manifest as artistic interventions, including musical concerts, competing with the State over regimes of representation. In this article I consider what these situated interventions reveal about the nature of borders in an age defined by the State’s paradoxical efforts to both materialize (as in the form of barrier building) and dematerialize (as in the form of data driven surveillance) state borders in defense of an increasingly elusive national sovereignty. To do so I examine a quartet of musical concerts staged at (or across) four national borders – Mexico/US; East/West Germany; North/South Korea; Columbia/Venezuela – to demonstrate how artists, activists, and even governments have attempted a type of performative spectacle which simultaneously stages and challenges sovereignty, undermining the border’s function as a limit and temporarily enacting a world without borders.